Activation of the Human Angiotensin-(1-12)-Chymase Pathway in Rats With Human Angiotensinogen Gene Transcripts - Ferrario, Carlos M.; VonCannon, Jessica; Ahmad, Sarfaraz; Wright, Kendra N.; Roberts, Drew J.; Wang, Hao; Yamashita, Tomohisa; Groban, Leanne; Cheng, Che Ping; Collawn, James F.; Dell'Italia, Louis J.; Varagic, Jasmina (Frontiers in Cardiovascular Medicine, 2019)
Angiotensin-(1-12) [Ang-(1-12)], an alternate substrate for tissue angiotensin II (Ang II) formation, underscores the importance of alternative renin-independent pathway(s) for the generation of angiotensins. Since renin enzymatic activity is species-specific, a transgenic model of hypertension due to insertion of the human angiotensinogen (AGT) gene in Sprague Dawley rats allowed for characterizing the contribution of a non-renin dependent mechanism for Ang II actions in their blood and heart tissue. With this in mind, we investigated whether TGR(hAGT)L1623 transgenic rats express the human sequence of Ang-(1-12) before and following a 2-week oral therapy with the type I Ang II receptor (AT1-R) antagonist valsartan. Plasma and cardiac expression of angiotensins, plasma renin activity, cardiac angiotensinogen, and chymase protein and the enzymatic activities of chymase, angiotensin converting enzyme (ACE) and ACE2 were determined in TGR(hAGT)L1623 rats given vehicle or valsartan. The antihypertensive effect of valsartan after 14-day treatment was associated with reduced left ventricular wall thickness and augmented plasma concentrations of angiotensin I (Ang I) and Ang II; rat and human concentrations of angiotensinogen or Ang-(1-12) did not change. On the other hand, AT1-R blockade produced a 55% rise in left ventricular content of human Ang-(1-12) concentration and no changes in rat cardiac Ang-(1-12) levels. Mass-Spectroscopy analysis of left ventricular Ang II content confirmed a >4-fold increase in cardiac Ang II content in transgenic rats given vehicle; a tendency for decreased cardiac Ang II content following valsartan treatment did not achieve statistical significance. Cardiac chymase and ACE2 activities, significantly higher than ACE activity in TGR(hAGT)L1623 rats, were not altered by blockade of AT1-R. We conclude that this humanized model of angiotensinogen-dependent hypertension expresses the human sequence of Ang-(1-12) in plasma and cardiac tissue and responds to blockade of AT1-R with further increases in the human form of cardiac Ang-(1-12). Since rat renin has no hydrolytic activity on human angiotensinogen, the study confirms and expands knowledge of the importance of renin-independent mechanisms as a source for Ang II pathological actions.